2023
DOI: 10.3390/biom13020206
|View full text |Cite
|
Sign up to set email alerts
|

The Essentials on microRNA-Encoded Peptides from Plants to Animals

Abstract: Primary transcripts of microRNAs (pri-miRNAs) were initially defined as long non-coding RNAs that host miRNAs further processed by the microRNA processor complex. A few years ago, however, it was discovered in plants that pri-miRNAs actually contain functional open reading frames (sORFs) that translate into small peptides called miPEPs, for microRNA-encoded peptides. Initially detected in Arabidopsis thaliana and Medicago truncatula, recent studies have revealed the presence of miPEPs in other pri-miRNAs as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…In planta interaction of peptides Mt-miPEP171b and sequence-unrelated Mt-miPEP171b2 to their common nascent pri-miRNA molecules has been shown by microscopic method (FRET-FLIM) and isothermal titration calorimetry. It has been suggested that this kind of protein–RNA binding strongly depends on the presence of a specific linear set of codons encoding interacting miPEP, but not a strongly conserved nucleotide sequence, so that non-conserved miPEPs can perform specific regulatory functions on their pri-miRNA species only [ 30 , 55 ].…”
Section: Subcellular and Molecular Targets Of Plant Mipepsmentioning
confidence: 99%
See 3 more Smart Citations
“…In planta interaction of peptides Mt-miPEP171b and sequence-unrelated Mt-miPEP171b2 to their common nascent pri-miRNA molecules has been shown by microscopic method (FRET-FLIM) and isothermal titration calorimetry. It has been suggested that this kind of protein–RNA binding strongly depends on the presence of a specific linear set of codons encoding interacting miPEP, but not a strongly conserved nucleotide sequence, so that non-conserved miPEPs can perform specific regulatory functions on their pri-miRNA species only [ 30 , 55 ].…”
Section: Subcellular and Molecular Targets Of Plant Mipepsmentioning
confidence: 99%
“…Assuming the peculiarities of interaction between miPEPs and their nascent pri-miRNAs [ 30 , 55 ], the following scheme for activation of pri-miRNAs by the encoded peptides has been proposed: miPEP translates in the cytoplasm from the full-length pri-miRNA or its fragment, containing ORF encoding miPEP; then, this peptide migrates to the nucleus, where it binds to the nascent pri-miRNA in the area of its coding sequence; such interaction further activates synthesis of the miRNA transcript at the transcription level [ 30 , 55 ]. However, the authors stress that there are some unanswered questions concerning the proposed mechanism.…”
Section: Possible Molecular Mechanisms Supporting Activity Of Plant M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Plant peptides are synthesized from precursor proteins or small open reading frames (sORFs) embedded within transcripts. These sORFs comprise 100 codons or less and lie either in the 5′‐leader sequence of a messenger RNA or are embedded within the primary transcripts of microRNAs (miRNAs) or are present within transcripts that code for short proteins of length <100 amino acids (Gautam et al, 2023; Hanada et al, 2013; Kumar et al, 2023; Lauressergues et al, 2015; Lauressergues et al, 2022; Ormancey et al, 2023; Sharma et al, 2020; Von Arnim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%